2014
DOI: 10.1093/ntr/ntu164
|View full text |Cite
|
Sign up to set email alerts
|

Framing Pictorial Cigarette Warning Labels to Motivate Young Smokers to Quit

Abstract: Introduction: The Family Smoking Prevention and Tobacco Control Act requires new pictorial warnings for U.S. cigarette packs, but enactment has been delayed by tobacco industry lawsuits. Research can inform implementation of the pictorial warning requirement and identify ways to optimize their public health impact post-implementation. This study investigated the impact of warning label message framing on young smokers' motivation to quit, examining cessation selfefficacy, and perceived risks as moderators of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 34 publications
3
29
0
3
Order By: Relevance
“…Then, participants completed outcome measures of behavioral intentions and their cognitive and emotional responses to the framed messages. All measures used items that were validated in prior research, including studies examining the effects of self-affirmation and message framing on related cancer risk behaviors (Mays, et al, 2014; Mays & Tercyak, 2015; Zhao & Nan, 2010). Outcome measures of behavioral intentions were similar to assessments of intentions to IT and intentions to quit IT administered before participants viewed the messages but were slightly adapted to avoid habituation that may occur due to the short timeframe of the experiment (Mays et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Then, participants completed outcome measures of behavioral intentions and their cognitive and emotional responses to the framed messages. All measures used items that were validated in prior research, including studies examining the effects of self-affirmation and message framing on related cancer risk behaviors (Mays, et al, 2014; Mays & Tercyak, 2015; Zhao & Nan, 2010). Outcome measures of behavioral intentions were similar to assessments of intentions to IT and intentions to quit IT administered before participants viewed the messages but were slightly adapted to avoid habituation that may occur due to the short timeframe of the experiment (Mays et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The study conducted to inform the U.S. Food and Drug Administration’s (FDA) selection of the final graphic warnings utilized self-reported emotional and cognitive reactions, recall, beliefs about the health risks of smoking, and intention to quit as outcomes, which are all explicit measures (Nonnemaker, Choiniere, Farrelly, Kamyab, & Davis, 2015). One small experimental study reported that exposure to the graphic warning labels that were high in emotional reactivity reduced the electrophysiological brain response to smoking cues (Wang, Lowen, Romer, Giorno, & Langleben, 2015), but other recent studies on the impact of the FDA’s final proposed graphic warnings have relied on self-reported explicit outcome measures (Cameron, Pepper, & Brewer, 2013; Cantrell et al, 2013; Hammond, Reid, Driezen, & Boudreau, 2013; Mays et al, 2014; Nonnemaker et al, 2015; Villanti, Cantrell, Pearson, Vallone, & Rath, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Konu ile ilgili çalýþmalarýn bulgularý zarar çerçeveli sigara uyarýlarýnýn yarar çerçeveli uyarýlara göre daha etkili olduðuna iþaret etse de, bu etkinin öz-yeterlilik ve sigara içmekle iliþkili risk algýsýna göre deðiþebileceði de öne sürülmektedir (31). Bulgular, bu öneriyi destekleyecek þekilde, yarar çerçeveli mesajlar (örn., sigarayý býrakmak kanser riskini azaltýr) yerine zarar çerçeveli mesajlara (örn., sigara içmek kansere neden olur) maruz kaldýk-larýnda, öz yeterliliði yüksek olan katýlýmcýlarýn düþük olanlara göre sigarayý býrakma niyetlerinin daha yüksek olduðunu göstermiþtir.…”
Section: Sigara Paketleri üZerindeki Uyarýlarýn ýçEriðiunclassified
“…Bulgular, bu öneriyi destekleyecek þekilde, yarar çerçeveli mesajlar (örn., sigarayý býrakmak kanser riskini azaltýr) yerine zarar çerçeveli mesajlara (örn., sigara içmek kansere neden olur) maruz kaldýk-larýnda, öz yeterliliði yüksek olan katýlýmcýlarýn düþük olanlara göre sigarayý býrakma niyetlerinin daha yüksek olduðunu göstermiþtir. Yarar çerçeveli mesajlara maruz kaldýklarýnda ise sigara ile ilgili risk algýsý yüksek olan katýlýmcýlarýn düþük olanlara göre sigarayý býrakma niyetlerinin daha yüksek olduðu bulunmuþtur (31)…”
Section: Sigara Paketleri üZerindeki Uyarýlarýn ýçEriðiunclassified
See 1 more Smart Citation